The Gamut of Renal Lesions on Autopsy: A Two-year Cross-sectional Study from North Eastern Odisha, India - Kalyani Prava Gouda; Upasana Das; Rashmi Rekha Mahapatra; Pragyan Lisha Panda; Lity Mohanty (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Kidney diseases have shown a rising upward trend in the last few decades due to the increase in incidence of associated chronic diseases like diabetes, hypertension. However the frequency and spectrum of renal pathology in autopsy specimens is not well documented or overlooked by physicians as well as pathologists. Aim: To analyse the spectrum of various types of renal pathologies, based on the histopathological analysis of renal tissue where autopsies were performed routinely with no history of renal diseases. Materials and Methods: This cross-sectional study was carried out over a period of two years from June 2021 to June 2023 in the Department of Pathology of SCB Medical College and Hospital, Cuttack, Odisha, India, and consisted of 84 cases of well-preserved renal autopsies. The autopsy samples were routinely processed and stained by Haematoxylin and Eosin (H&E) and then reported. Special stain of Periodic Acid Schiff (PAS) was done. Gross and microscopic findings were studied. The study was compared with other relevant studies. The data was analysed using Microsoft Excel 2019. Results: A total of 84 cases were included in the study. The male:female ratio was 1.27:1. The age group with the highest number of cases (35 cases) was 21-40 years. Among the 84 cases the commonest pathology was seen in tubules (40 cases, 47.62%) and glomeruli (7 cases, 8.33%), followed by vascular pathologies (5 cases, 5.95%) and interstitial lesions (4 cases, 4.76%). Renal cell carcinoma was incidentally detected in two cases and Wilms tumour in one case. Five cases had normal histology. Conclusion: The study illuminates the various renal lesions on autopsy and showed tubular lesions were more common than glomerular lesions in renal autopsy. Renal lesions are more common in males. The focus should be to develop more effective diagnostic methods for renal lesions so that intervention can be fast and sharp resulting in less mortality.